2022
DOI: 10.11604/pamj.2022.42.47.31439
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of obstetric caregivers towards labor pain relief methods and associated factors at public health centers of East Gojjam zone, Amhara Region, Ethiopia: Institutional based cross-sectional study

Abstract: Introduction labour pain relief is a key factor for maternal satisfaction during childbirth. However, in developing countries, labour pain management is not a well-established service mainly due to negative attitudes of health care providers resulting in unmeasured suffering from childbirth for mothers. Thus, this study was aimed to assess attitude of obstetric caregiver towards labour pain management and associated factors at public health centers of East Gojjam zone. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…There is a wide range of factors which may influence labor pain, including emotional feelings, mothers' expectations, physical and personal characteristics associated with the women in labor. 2,[15][16][17] Though labor pain management measures are accepted and implemented in many countries around the world, in low-resource settings, the provision of pain relief during childbirth is often neglected. For instance, this is the case in Ethiopia, a country with low institutional delivery rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide range of factors which may influence labor pain, including emotional feelings, mothers' expectations, physical and personal characteristics associated with the women in labor. 2,[15][16][17] Though labor pain management measures are accepted and implemented in many countries around the world, in low-resource settings, the provision of pain relief during childbirth is often neglected. For instance, this is the case in Ethiopia, a country with low institutional delivery rates.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also showed that despite improvement in the development of standards for pain assessment and treatment, labor pain is mostly ignored especially in low‐ and middle‐income countries resulting in unmeasured suffering from childbirth for mothers. There is a wide range of factors which may influence labor pain, including emotional feelings, mothers' expectations, physical and personal characteristics associated with the women in labor 2,15–17 …”
Section: Introductionmentioning
confidence: 99%